Effect of Yoga Physical Activity on Increasing Self-Control and Quality of Life - Rahayu, Nur Indri; Amalia, Triska Pangestu; Damayanti, Imas (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The purpose of this study was to determine the effect of physical activity of yoga on improving self-control and quality of life. The method used is experimental with The One-Group Pretest-Posttest Design research design. The sample of this research is the active female students of UPI Sport Science with a total sample of 28 people. The sampling technique uses purposive sampling. The instrument used was an adaptation of the Self-Control Scale questionnaire to test the increase in self-control and WHOQOL-100 to test the increase in quality of life. Data analysis used was Paired Sample t-Test to test the effect of yoga physical activity on increasing self-control and quality of life. The results of data analysis showed that there was an influence of physical activity of yoga on the increase in self-control (Z = -3,343, p = 0.001) and quality of life (t = -3.663, p = 0.001). So, it can be concluded that there is an influence of physical activity of yoga on increasing self-control and quality of life.